The INFLUENCE OF INFLUENCER MARKETING AND ONLINE CUSTOMER REVIEWS ON PURCHASE DECISIONS FOR SKINTIFIC PRODUCTS IN THE E-COMMERCE TIKTOK SHOP - Ar Kacio Maharani; Musnaini; Ade Perdana Siregar (Journal of Business Studies and Management Review, 2025)
This study aims to determine the influence of influencer marketing and online customer reviews on purchasing decisions for Skintific products on the TikTok Shop e-commerce platform. The background of this study is based on the increasing use of TikTok as a marketing platform and the large number of Generation Z consumers who purchase skincare products after seeing promotions from influencers and reviews from other users. The research method used is associative quantitative research with data collection techniques through distributing questionnaires to 200 respondents who are TikTok Shop users and have purchased Skintific products via WhatsApp. Data analysis was carried out using multiple linear regression with the help of SPSS software. The results show that both influencer marketing and online customer reviews have a positive and significant effect, both partially and simultaneously, on purchasing decisions. The conclusion of this study is that marketing strategies involving influencers and online reviews can influence consumer behavior, especially in purchasing decisions on digital platforms. This research is expected to provide practical contributions for business actors and academics in the development of digital marketing studies.